Novel poly (ADP‐ribose) polymerase inhibitor, AZD2281, enhances radiosensitivity of both normoxic and hypoxic esophageal squamous cancer cells. Issue 3 (21st January 2015) - Zhan, L.; Qin, Q.; Lu, J.; Liu, J.; Zhu, H.; Yang, X.; Zhang, C.; Xu, L.; Liu, Z.; Cai, J.; Ma, J.; Dai, S.; et al.
Summary: Radiotherapy plays an important role in the treatment of esophageal squamous cell carcinoma (ESCC). However, the outcome of radiotherapy in ESCC remains unsatisfactory because esophageal squamous cancer cells, particularly those under hypoxic condition, exhibit radioresistance. The aim of this study was to determine whether or not AZD2281, a potent poly (ADP‐ribose) polymerase (PARP) inhibitor, could enhance the radiation sensitivity of two ESCC cell lines, namely ECA109 and TE13. The radiosensitizing effect of AZD2281 was evaluated on the basis of cell death, clonogenic survival and tumor xenograft progression. AZD2281 alone was slightly toxic to ESCC cell lines. Apoptosis was increased and clonogenic survival was decreased in both cell lines when AZD2281 was combined with ionizing radiation (IR) under normoxic condition. AZD2281 enhanced IR‐induced apoptosis to a more significant level under chronic hypoxic condition (0.2% O2, 48 hour) than under normoxic condition. AZD2281 also slightly enhanced clonogenic cell death under chronic hypoxic condition compared with that under normoxic condition. This result could be associated with increased radiation‐induced DNA double‐strand breaks (DSB), decreased DSB repair and increased apoptosis of ESCC cells. Furthermore, homologous recombination (HR) protein Rad51 expression and focus formation were decreased in ESCC cells exposed to moderate chronic hypoxic condition (0.2% O2, 48 hour); this result indicated that chronic hypoxic ESCC cells were HR deficient, possibly causing contextual synthetic lethality with PARP inhibitor in radiation sensitization. AZD2281 was also a radiation sensitizer in ESCC tumor xenograft models. Hence, in vitro and in vivo findings provide evidence that AZD2281 potently sensitizes ESCC cells to X‐ray irradiation. The selective cell killing of HR‐defective hypoxic cells contributes to radiosensitization by PARP inhibitor in ESCC cells under hypoxic condition.